Plasma-derived phosphoglycerate mutase 5 as a biomarker for Parkinson’s disease - Feng, Liang; He, Haijun; Xiong, Xi; Xia, Kai; Qian, Shuangjie; Ye, Qianqian; Feng, Feifei; Zhou, Shuoting; Hong, Xianchai; Liu, Yiming; Xie, Chenglong (Frontiers in Aging Neuroscience, 2022)
Background We aimed to examine whether plasma-derived phosphoglycerate mutase 5 (PGAM5) can be a biomarker for Parkinson’s disease (PD) diagnosis as well as its association with the severity of motor/non-motor manifestations of PD. Methods We enrolled 124 patients with PD (PD group) and 50 healthy controls (HC group). We measured plasma PGAM5 levels using a quantitative sandwich enzyme immunoassay. Patients with PD underwent baseline evaluations using the Unified Parkinson’s Disease Rating Scale (UPDRS), while participants in both groups were evaluated using scales for non-motor manifestations. Receiver operating characteristic curves were used to evaluate the predictive utility of plasma PAMG5 alone and combined with other factors. Results Plasma PAMG5 levels were significantly higher in the PD group; the area under the curve (AUC) of plasma PGAM5 levels alone was 0.76. The AUC values for elderly participants and patients without hypertension were 0.78 and that for was 0.79. Notably, plasma PGAM5 levels combined with plasma oligomeric α-synuclein (α-syn) and the score of the REM sleep behavior disorder questionnaire-Hong Kong (RBDQ-HK) showed AUC values of 0.80 and 0.82. Multivariable logistic analysis revealed that plasma PAMG5 levels were independently associated with PD (odds ratio,1.875 [95% confidence interval 1.206–2.916], p = 0.005) but not the severity of motor/non-motor manifestations of PD. Conclusion Plasma PGAM5 is an independent biomarker for PD, especially among elderly patients (age > 60 years) and patients without hypertension. The predictive utility of PGAM5 was improved when combined with plasma oligomeric α-syn or the RBDQ-HK score.